Social, Academic and Health Status Impact of Long COVID on Children and Young People: An Observational, Descriptive, and Longitudinal Cohort Study - Alba Gonzalez-Aumatell; Maria Victoria Bovo; Clara Carreras-Abad; Sara Cuso-Perez; Èlia Domènech Marsal; Roser Coll-Fernández; Aroia Goicoechea Calvo; Maria Giralt-López; Antonia Enseñat Cantallops; Sara Moron-Lopez; Javier Martinez-Picado; Paula Sol Ventura; et al. (MDPI AG, 2022)
There is a lack of evidence of the health impacts due to long COVID among children and young people (CYP). The objective of this study is to determine the main clinical characteristics of long COVID in CYP and to investigate the academic, social, and health status impacts of long COVID in this population. An observational, descriptive, and longitudinal study on CYP who presented COVID-19 symptoms for more than twelve weeks after SARS-CoV-2 infection was performed between December 2020 and May 2021. Fifty CYP were included, with a median age of 14.1 years, 33 (66%) were female, and 17 (34%) had a relative diagnosed with long COVID. Since the initial infection and up to the first visit, CYP had persisting symptoms for a median of 4.1 months, and for 18 (36%) CYP these symptoms persisted for more than 6 months. Fatigue (100%), neurocognitive disorders (74%), muscular weakness (74%), and headache (72%) were the most reported symptoms. A total of 9 (18%) CYP could not attend school, 17 (34%) had a reduced schedule, 33 (66%) showed a decreased school performance, and 68% had stopped extracurricular activities. This preliminary study shows the impact that long COVID has on the health, academic, and social life of CYP.